Dual In Situ Polymerization Strategy Endowing Rapid Ion Transfer Capability of Polymer Electrolyte toward Ni‐Rich‐Based Lithium Metal Batteries. Issue 8 (22nd June 2022) - Wang, Su; Sun, Qifang; Ma, Yue; Wang, Zhenyu; Zhang, Hongzhou; Shi, Xixi; Song, Dawei; Zhang, Lianqi; Zhu, Lingyun
Abstract: Poly(vinylidenefluoride‐ co ‐hexafluoropropylene) (PVDF‐HFP) is one of the most promising candidate electrolyte matrices for high energy batteries. However, the spherical skeleton structure obtained through the conventional method fails to build continuous Li ion transmission channels due to the slow volatilization of high boiling solvent, leading to inferior cycling performance, especially in a Ni‐rich system. Herein, a novel strategy is presented to enrich the Li ion transfer paths and improve the Li ion migration kinetics. The tactic is to prepare cross‐linked segments through the PVDF‐HFP matrix by adopting free radical polymerization and Li salt induced ring‐opening polymerization. Most significantly, the visualization of the structure of as‐prepared electrolyte is innovatively realized with the combination of polarization microscopy, transmission electron microscopy, scanning electron microscope‐energy dispersive spectroscopy, PVDF‐HFP, and cross‐linked network form interconnected microstructures. Therefore, poly(glycidyl methacrylate and acrylonitrile)@poly(vinylidene fluoride‐hexafluoropropylene) electrolyte presents a high ionic conductivity (1.04 mS cm −1 at 30 °C) and a stable voltage profile for a Li/Li cell after 1200 h. After assembly with a LiNi0.8 Co0.15 Al0.05 O2 cathode, a high discharge specific capacity of 190.3 mAh g −1 is delivered, and the capacity retention reaches 88.2% after 100 cycles. This work provides a promising method for designing high‐performance polymer electrolytes for lithium metal batteries. Abstract : A cross‐linked glycidyl methacrylate‐acrylonitrile network is constructed through poly(vinylidenefluoride‐ co ‐hexafluoropropylene) matrix by adopting free radical polymerization and ring‐opening polymerization. The structure of poly(glycidyl methacrylate and acrylonitrile)@poly‐(vinylidene fluoride‐hexafluoropropylene) can be visualized by polarization microscopy. Enabled by the introduction of successive Li ion transfer paths and the dual in‐situ polymerization strategy, excellent electrochemical performances are achieved.